Sosialisasi Cara Berbisnis Secara Syariah Lewat E-commerse Bagi Siswa SMA Islam Yaspia Cibarusah - MH Ainulyaqien; Sakum; Sarwo Edy; Djoko Nugroho; Siti Juariah (DPPM Universitas Pelita Bangsa, 2021)
Sharia business refers to a type of business that operates according to Islamic sharia principles. These principles include the prohibition of usury (interest), maysir (gambling), gharar (uncertainty or lack of clarity), and activities that are religiously forbidden. The main objective of sharia business is to create justice, sustainability and prosperity for society. In Indonesia, there are several levels of schools consisting of SD (Elementary School), SMP (Junior High School), SMA (High School), and SMK (Vocational High School). One of the high school schools in Indonesia is Yaspia Cibogo Cibarusah Islamic High School. Today's technological developments are increasing rapidly, the benefits of technological sophistication can be used to improve the people's economy by buying and selling online or known as e-commerce. The increase in e-commerce business is expected to help the business development of micro, small and medium enterprises (MSMEs). The purpose of this writing is to find out how MSME e-commerce can survive during a pandemic by using an analysis of economic dominance (wallerstein). This study uses a library research approach by processing primary data on e-commerce studies, including books, journals, theses, dissertations and other newspapers. The results of this study indicate that E-commerce is one of the best alternatives to encourage business independence, especially when facing an economic recession during the Covid 19 pandemic. The use of e-commerce can be done to expand market access, create jobs and have a positive impact on various other supporting e-commerce business sectors which in turn can contribute to accelerating Indonesia's economic growth. In conclusion, sharia business through e-commerce offers an attractive potential in providing fair, transparent and ethical business solutions. By leveraging digital technology, Islamic businesses can reach more customers and expand their social impact. However, support from the government, sharia institutions and other stakeholders is essential to ensure an ecosystem that is conducive to the development of sustainable and inclusive sharia e-commerce.